Infrastructure and manufacturing in Sub-Saharan Africa: An empirical analysis using dynamic panel data models - Bovick Wandja Yemba; Rafael Saulo Marques Ribeiro; Victor Medeiros (PSL Quarterly Review, 2020)
The provisioning of adequate infrastructure may be seen as a key contributing factor in the industrialization process as well as economic development across the globe. While there is a vast empirical literature assessing the impact of infrastructure on economic growth, productivity and income inequality, estimates of the effect on infrastructure on manufacturing sector, in particular, are rather scant. Using dynamic panel data models, we empirically investigate the impact of investments in power, transportation and telecommunication sectors on the manufacturing industry for a sample of 48 Sub-Saharan African countries over the 1980-2012 period. Our findings suggest a positive effect of infrastructure provisioning on industrialization in the region.
Keywords: H54; O14; O55; 330; infrastructure; industrialization; Sub-Saharan Africa